2005
DOI: 10.1097/01.mib.0000186408.07769.78
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Treatment Does Not Induce Organ-specific or Nonorgan-specific Autoantibodies Other than Antinuclear and Anti-Double-Stranded DNA Autoantibodies in Crohnʼs Disease

Abstract: The humoral response induced by infliximab was restricted to ANA and anti-dsDNA autoantibodies, which persist for up to 1 year of follow-up. We confirmed the significant prevalence of such autoantibodies induced by infliximab in CD, but they are not generally associated with clinical signs of autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…A small study including 35 infliximab-treated CD patients and 32 CD patients without infliximab treatment showed in 14.3% of CD patients ANA titers of 1:160 before infliximab treatment which increased to 45.7% after 24 months of infliximab treatment. 27 This was very similar to the 44.4% ANA-positive patients found in our study. In the control population 18.8% of the CD patients were ANApositive.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A small study including 35 infliximab-treated CD patients and 32 CD patients without infliximab treatment showed in 14.3% of CD patients ANA titers of 1:160 before infliximab treatment which increased to 45.7% after 24 months of infliximab treatment. 27 This was very similar to the 44.4% ANA-positive patients found in our study. In the control population 18.8% of the CD patients were ANApositive.…”
Section: Discussionsupporting
confidence: 90%
“…In the control population 18.8% of the CD patients were ANApositive. 27 The same study showed dsDNA antibodies in one patient (3%) at baseline and in 35% after 1 year of infliximab treatment, while none of the control patients (without infliximab treatment) became dsDNA-positive. 27 In another small study including 36 CD patients treated with infliximab, 22.2% were ANA-positive at baseline.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A signicant percentage of patients treated with anti-TNF therapy develop positive anti-nuclear antibodies and a smaller proportion develop antibodies to double-stranded DNA (148,150) . e development of symptomatic disease (i.e., drug-induced lupus) is distinctly unusual and no patient has developed renal or central nervous system involvement (155) .…”
Section: Severe / Fulminant Diseasementioning
confidence: 99%
“…It was reported that development of ANA and anti-dsDNA antibodies is seen during the course of anti-TNF- therapy in patients with some autoimmune diseases such as rheumatoid arthritis [32][33][34], psoriasis [35], Crohn's disease [36], and BD [22]. In the present study, 75.0% of the patients converted to ANA-positive during the course of IFX therapy and positive ANA titres (1: 80) had been detected in one patient on study enrolment.…”
Section: Discussionmentioning
confidence: 99%